Pengaruh Green Finance terhadap Keputusan Investasi pada Sektor Energi Baru Terbarukan di Bursa Efek Indonesia - Sari, Amilia Paramita (Universitas Batanghari, 2024)
The present study investigates the impact of green financing rules on investment decisions made by investors in the Indonesia Stock Exchange-listed New and Renewable Energy sector. The move toward cleaner energy is being fueled in large part by green finance due to the growing focus on sustainability and its effects on the environment. Using a census approach to gather data from the financial statements of firms in the New and Renewable Energy Sector, simple linear regression analysis is the research method employed, along with the green finance policies that are relevant in Indonesia. The study's findings demonstrate that green financing has a major and favorable impact on this industry's investment choices. Additionally, businesses that employ green financing are more likely to do financially well, which draws in additional investors. This finding highlights the significance of putting more targeted measures into place to support green finance investment in order to meet sustainability and economic growth objectives in the New and Renewable Energy Sector, which has important ramifications for investors and policymakers.